APTES Functionalization of cGNP Electrochemical Immunosensor for Detection of Immunoglobulin G - Mohd Azmi, Mohd Azraie; Fatihatul Zuriati Makmon; Nur Azura Mohd Said; Hazana Razali; Mohd Ifwat Mohd Ghazali; Shahino Mah Abdullah; Owen J Guy (International Journal of Integrated Engineering, 2024)
This paper demonstrates the development of carbon-based graphene nanoplatelet (cGNP) electrochemical immunosensor for detection of Immunoglobulin G (IgG). Initially, surface characterization via SEM revealed a smooth surface on the cGNP indicating successful GNP coverage using the drop-casting method. Screening of electrolyte buffers revealed that ferrocyanide and ferricyanide provided a favorable response with a current density of 9.369 µA. Functionalization of cGNP, was achieved using a 2% APTES solution during a 1-hour incubation period. Electrochemical characterization through cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) demonstrated excellent electrochemical activity when 0.1% bovine serum albumin (BSA) was employed as a blocking agent against 1 mg/ml IgG. Chronoamperometry (CA) confirmed IgG immobilization at a potential of 0.1 V. Notably, the immobilization of IgG resulted in an increase in the charge transfer resistance (Rct) to 69.8 ± 2.3 ?, attributed to the hindrance of biological molecules on interfacial electron transfer. Consequently, the proposed cGNP electrochemical immunosensor platform exhibited a robust analytical response, characterized by optimal antibody binding capacity. This superior performance can be attributed to the presence of GNP on the screen-printed carbon electrode (SPCE), which enhanced surface area, conductivity, and overall electrical properties. These attributes make this platform a promising candidate for further research in protein biomarker diagnosis and related applications.